The Effect of Growth Medium Strength on Minimum Inhibitory Concentrations of Tannins and Tannin Extracts against E. coli - Štumpf, Sara (Molecules, 2020)
In this study the effect of growth medium strength on the minimum inhibitory concentration (MIC) of different tannins and tannin extracts against Escherichia coli was systematically investigated for the first time. Three pure compounds (vescalagin, castalagin and gallic acid) and five extracts (chestnut, quebracho, mimosa, Colistizer and tannic acid) were studied. Broth microdilution was assayed and bacteria were grown using different growth medium strengths varying from half to double the concentration recommended by the producer. MICs were determined using the iodonitrotetrazolium chloride (INT) dye or turbidity measurements. It was observed that MIC values depend on the growth medium strength. With an increase in the growth medium concentration MIC values rose roughly linearly for all samples, while their relative order remained unchanged, indicating that a direct interaction of tannins with growth medium nutrients represents the likely source of their antimicrobial activity. Understanding the effect of growth medium strength can finally yield a plausible explanation for the observed variation in MIC values reported in the scientific literature as well as provide help in planning proper applications of tannins in the livestock production.